2022
DOI: 10.3389/fnetp.2022.849253
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mechanisms Underlying Cirrhotic Cardiomyopathy

Abstract: Cardiac dysfunction associated with cirrhosis in the absence of preexisting heart disease is a condition known as cirrhotic cardiomyopathy (CCM). Cardiac abnormalities consist of enlargement of cardiac chambers, attenuated systolic and diastolic contractile responses to stress stimuli, and repolarization changes. CCM may contribute to cardiovascular morbidity and mortality after liver transplantation and other major surgeries, and also to the pathogenesis of hepatorenal syndrome. The underlying mechanisms of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 100 publications
0
23
0
3
Order By: Relevance
“… 24-26 Además, los ácidos biliares en exceso estimulan los receptores muscarínicos M2, lo que reduce la producción de AMPc intracelular y disminuyen la contractilidad cardíaca y pueden provocar arritmias. 25 Por otro lado, la disfunción contráctil ocurre por una inversión en el consumo metabólico de ácidos grasos y glucosa por el miocardio y los ácidos biliares en exceso alteran esta relación de la oxidación de sustratos: mayor oxidación de glucosa y menos de ácidos grasos (la inversa es lo normal). En las membranas de los cardiomiocitos, hay una alteración de la relación colesterol:fosfolípidos, lo que produce rigidez de la membrana y alteración del funcionamiento de los receptores β-adrenérgicos y disminución de la producción intracelular de AMPc.…”
Section: Resultsunclassified
“… 24-26 Además, los ácidos biliares en exceso estimulan los receptores muscarínicos M2, lo que reduce la producción de AMPc intracelular y disminuyen la contractilidad cardíaca y pueden provocar arritmias. 25 Por otro lado, la disfunción contráctil ocurre por una inversión en el consumo metabólico de ácidos grasos y glucosa por el miocardio y los ácidos biliares en exceso alteran esta relación de la oxidación de sustratos: mayor oxidación de glucosa y menos de ácidos grasos (la inversa es lo normal). En las membranas de los cardiomiocitos, hay una alteración de la relación colesterol:fosfolípidos, lo que produce rigidez de la membrana y alteración del funcionamiento de los receptores β-adrenérgicos y disminución de la producción intracelular de AMPc.…”
Section: Resultsunclassified
“…An area of controversy remains as to whether decreased HRV is as a result of defective cardiomyocyte responsiveness, this is since cytokines have been found to diminish beta‐ adrenergic signaling, resulting in pronounced adrenergic hypo‐responsiveness (Gaskari et al, 2006 ; Prabhu, 2004 ), known as cirrhotic cardiomyopathy. Cirrhotic cardiomyopathy is indeed a frequent complication exhibited in cirrhosis, resulting in defective contractile activity of the myocardium in response to physiological stress and stimulation (Myers & Lee, 2000 ), however, is nonetheless difficult to diagnose due to the profound systemic vasodilation exhibited in cirrhosis, concealing the presence of cardiomyopathy (Liu et al, 2017 , 2022 ). Several mechanistic theories have indeed been proposed such as abnormalities in the cardiomyocyte membrane, as well as an increased biosynthesis of nitric oxide (NO), and other mediators such as carbon monoxide and endocannabinoids eliciting a role in its pathogenesis (Gaskari et al, 2005 ; Yoon et al, 2020 ), Thus, given that NO has been found to be pivotal in the pathogenesis of the impaired cardiac adrenergic response exhibited in cirrhosis, whether this manifestation contributes to the reduction of HRV in patients, is yet to be more accurately ascertained.…”
Section: Heart Rate Variability In Cirrhosismentioning
confidence: 99%
“…The background for LVDD in the setting of cirrhosis is increased stiffness of the myocardial wall owing to myocardial hypertrophy, fibrosis, and subendothelial edema [6]. Among the potential pathogenetic mechanisms of cirrhosis-related LVDD, the role of inflammatory activity has attracted growing interest [7]; however, supporting evidence of this association remains limited [8,9]. The presence of LVDD in patients with cirrhosis has been suggested to predispose to development of acute renal dysfunction [10] and HRS [11,12].…”
Section: Introductionmentioning
confidence: 99%